Король хитрости: сборник рассказов / Д. А. Емец - Емец Дмитрий Александрович (Любимые книги Тани Гроттер, 2004)
Экземпляры: (20181205) / Инвентарный номер: 41558 / Цена: 81.18 / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: Е 60 / ББК: 84(2Рос=Рус)6